ANALISIS KRITIS TERHADAP PEMENUHAN HAK ASASI MANUSIA BAGI NARAPIDANA PEREMPUAN HAMIL DAN MENYUSUI DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Firmansyah, Muhammad Rafly (Ensiklopedia of Journal, 2024)
This research critically analyzes the fulfillment of human rights for pregnant and breastfeeding female prisoners in correctional institutions. The urgency of this study arises from the need to address the significant gaps in legal protections and healthcare provisions for this vulnerable group. Utilizing qualitative methods, including interviews and document analysis, the research reveals systemic deficiencies in meeting their rights, particularly regarding maternal health care and child welfare. The findings indicate that many female inmates face inadequate support, which compromises their health and that of their infants. This study underscores the necessity for policy reforms to enhance human rights protections for incarcerated women, ensuring their dignity and well-being during pregnancy and breastfeeding.Keywords: human rights; female prisoners; maternal health; incarceration; policy reform.